2012
DOI: 10.1155/2012/907179
|View full text |Cite
|
Sign up to set email alerts
|

Alveolar Soft Part Sarcoma: A Single-Center 26-Patient Case Series and Review of the Literature

Abstract: Background. Alveolar soft part sarcoma (ASPS) is a rare tumor, and little information is available regarding its clinical features and appropriate treatments. Methods. A retrospective review of 26 consecutive ASPS patients (12 male, 14 female; mean age of 27 years) treated at our institution over 30 years (mean followup; 71 months) was performed. Results. The primary tumor developed in the lower extremity (12), trunk (8), and upper extremity (6), with an average size of 7.2 cm (range, 2–14 cm). The AJCC stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
82
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(89 citation statements)
references
References 26 publications
4
82
1
Order By: Relevance
“…The tumor was well enhanced on contrast-enhanced CT and MRI, and exhibited vascular signal voids. These reliable radiologic findings are well correlated with the high vascularity of ASPS in pathological specimens (10).…”
Section: Discussionsupporting
confidence: 52%
“…The tumor was well enhanced on contrast-enhanced CT and MRI, and exhibited vascular signal voids. These reliable radiologic findings are well correlated with the high vascularity of ASPS in pathological specimens (10).…”
Section: Discussionsupporting
confidence: 52%
“…ASPS has a slight female predilection in younger patients, which is hypothesized to be caused by an extra X chromosome that may be susceptible to mutation [10]. However, there is a male preponderance in older patients [5,11]. Despite all the latest findings, the origin of ASPS is still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The frequency of brain metastases is almost three times higher than in other sarcomas. In most cases they are associated with other extracranial metastases, such as lungs and bones [5,11]. The frequency of local recurrence varies among large studies between 10% and 31% [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Differences in biologic characteristics of pediatric and adult ASPS have been proposed as a possible explanation. 15 In a case-series study reported by Ogura et al, 29 pediatric tumors tended to be smaller than those in adult patients, with the larger tumor size resulting in increased risk of distant metastasis. Radical resection is the treatment of choice for localized disease.…”
Section: Treatment and Prognosismentioning
confidence: 95%